Recent Advances on the Adsorption of Pollutants from Aqueous Media Using Clay-Based Adsorbents - Oreofe, Toyin Adedayo; Arinkoola, Akeem Olatunde; Bello, Solomon Olugbenga; Ogunleye, Oladipupo Olaosebikan (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
The sequestration of pollutants from wastewater remains an active research topic recently owing to persistent disposal of industrial wastewater to waterbodies without adequate management strategies available especially in the developing countries. Different technologies have been employed in which adsorption has found a wide range of application. Today, various low cost adsorbents have been developed and evaluated for the adsorption processes. Clay mineral is one of the low cost natural adsorbents requiring minimum modification to enhance its adsorptive capacities. To maintain a clean and safe environment the water bodies must be free of contaminants of emerging concern. The availability of potable water is a global effort, as two of the UN's seventeen Sustainable Development Goals (SDG) are centered on water which is not surprising. Goal 6 focuses on clean water and sanitation whereas Goal 14 focuses on life below the water. With this in view, the availability of potable water highlights the significance of this study, which analyzes the potential of clay minerals as a good precursor for water treatment. Therefore, this review focuses on the clay minerals, its availability in Nigeria, classification and modification of the clay adsorbent.